النظائر المخادعة بين اللغة العربية والأتشيهية في قاموس اللغة الأتشيهية و الاستفادة منها في تعليم اللغة العربية لللأتشيهين من مادة الحرف كا بموذجا - WAHYUDI RUS; MUHAMMAD AL-MUSTAFA ABDUL JABBAR (Lembaga Penelitian dan Pengabdian Masyarakat, Sekolah Tinggi Ilmu Bahasa Arab Ar Raayah, 2016)
This study aims to averment the existence of banjar’s words borrowed from the Arabic language in (Aceh-Indonesia Dictionary) by Abi Bakar, and collection and analysis these words according to the eir meaning and pronunciation, and its use in simplification process of the teaching Arabic for Acehneses.The result indicated that there are fifty four homophones between Arabic and Acehnese. Those homophones were figured out in the dictionary of Acehnese–Indonesia and some arabic dictionaries. Of these 54 homophones, there are several words in Acehnese language which are frequently pronounciated by Acehnese people in daily speaking and some others of the homophones are rare. As for the method used in teaching Arabic to the Acehnese people , it can be done through by presenting pictures related to the sentence to explain its meaning or partly in text reading, dialogue, or practice. This research showed that Accehnese people are able to recognize the Arabic language from the homophones.